Biomechanics and bioenergetics of 100-m front crawl swimming in young male swimmers - Latt, E.; Jurimae, J.; Maestu, J.; Purge, P.; Ramson, R.; Keskinen, K. L.; Haljaste, K.; Jurimae, T. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: No studies have investigated the influence of somatic, energetic and technical parameters together to determine sprint swimming performance in boys after reaching puberty. The purpose of the study was to analyze possible relationships between swimming performance, anthropometrical, physiological and biomechanical parameters in male adolescent swimmers. METHODS: 25 male swimmers (15.2+/- 1.9years; 176.1+/-9.2 cm; 63.3+/-}10.9 kg) performed 100m maximal front crawl swim in the 25m pool. Oxygen consumption, swimming speed ( ), stroke rate (SR), stroke length (SL) and stroke index (SI) were assessed. Blood samples for lactate were taken at the 3rd and 5th minute of recovery and energy cost (Cs) was calculated. RESULTS: The average 100-m performance time was 77.6+/-}9.1 and was significantly related (p<0.05) to height, body mass and arm span values from the measured somatic parameters and to ~, SL, SR and SI values, and VO2, ƒ¢La and Cs values from measured biomechanical and bioenergetic parameters. Biomechanical factors (79%) characterized best the 100m swimming performance in these young swimmers, followed by somatic (49%) and bioenergetic factors (32%). DISCUSSION: The most important finding was that biomechanical parameters characterized best the 100m swimming performance, while the SI was the best predictor of sprint performance in adolescent male swimmers. Therefore, learning the correct swimming technique from the early years of swimming training is important. Cs is a key parameter to evaluate performance in swimming, but there are only a few studies that have investigated the determinants of swimming economy in children and adolescents (Kjendlie et al. 2004; Poujade et al. 2002). By investigating how aerobic and anaerobic performance develops during growth and maturation, it may be possible to identify the capacity for improvement and provide guidelines to coaches for the preparation of specific training sessions for young swimmers.